2009
DOI: 10.1158/1055-9965.epi-08-0682
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in Maori, Asian, and Pacific Peoples in New Zealand

Abstract: New Zealand Maori, Pacific, and Asian people develop melanoma less frequently than New Zealand Europeans, but little is known about melanomas that develop in these people. We examined the characteristics of melanoma in these minority ethnic groups in New Zealand. In 2007, all first primary melanomas diagnosed from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…We have previously reported an association between perceived risk of developing skin cancer and sun-protective behaviors among a sample of outdoor workers (18). A recently published study found increases in melanoma among the Maori and Pacific populations of NZ (19), and although we know that there is a range of skin types among Maori (20), further research is required into whether the dark shift phenomenon may have contributed to these outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported an association between perceived risk of developing skin cancer and sun-protective behaviors among a sample of outdoor workers (18). A recently published study found increases in melanoma among the Maori and Pacific populations of NZ (19), and although we know that there is a range of skin types among Maori (20), further research is required into whether the dark shift phenomenon may have contributed to these outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…In the state of Texas, skin cancer rates were approximately five times greater for light-skinned people compared with dark-skinned people. Other studies in Australia and New Zealand compared skin cancer rates of light-skinned individuals to aboriginal residents (e.g., Haynes et al, 2008;Sneyd and Cox, 2009;Olsen et al, 2012). The results were consistently the same: lighter-skinned individuals had higher skin cancer rates.…”
mentioning
confidence: 69%
“…Like all skin cancers, lightly pigmented populations are at greater risk of developing CMM, although it is present in more darkly pigmented populations in lower proportions (Table 1; also see Camain et al, 1972;Soeripto et al, 1977;Bang et al, 1987;Neugut et al, 1994;Yakubu and Mabogunje, 1995;Sneyd and Cox, 2009). Accordingly, one cannot easily dismiss skin cancer as a selective pressure in the adaptation to UVR.…”
Section: Skin Cancer Typesmentioning
confidence: 99%
“…Outlook for patients with thin invasive melanoma is positive, although continued clinical vigilance is warranted for patients with nodular melanoma and those with the thickest tumors (Green et al, 2012). Cutaneous melanoma is much less common among Maori than among New Zealand Europeans, but Maori have a greater Breslow depth and therefore have a worse prognosis (Hore et al, 2010) Minority ethnicities in New Zealand have a higher than expected risk of thick and more advanced melanoma, with poorer prognosis (Sneyd and Cox, 2009). …”
Section: Skinmentioning
confidence: 99%